Anti-Diabetes Mellitus Plants: Active Principles, Mechanisms of Action and Sustainable Utilization - Appian Subramoniam (CRC Press, 2017)
The incidence and severity of diabetes mellitus is increasing worldwide, presenting a significant burden to society both in economic terms and overall well-being. There is a growing demand for novel safe and effective medicines due to the limited efficacy and undesirable side effects of current conventional drugs. We now have a great opportunity to develop plant-based therapies for diabetes mellitus with superior efficacy and safety utilizing modern science and technology. Anti-Diabetes Mellitus Plants: Active Principles, Mechanisms of Action and Sustainable Utilization begins with a detailed introduction to diabetes mellitus including current treatments for this disease in conventional medicine. It provides an authoritative overview of available methods for studying the anti-diabetes mellitus activities of plant products. The book highlights the likely therapeutic superiority of scientifically developed combinations of anti-diabetes mellitus phytochemicals and polyherbal formulations. This unique reference covers the development of polyherbal formulations and conventional combination drugs with desired targets of action for diabetes mellitus patients. In this book, more than 300 anti-diabetes phytochemical compounds are extensively covered and updated with their pharmacological properties. It will serve as a valuable source of information for researchers, students, doctors, biotechnologists, diabetic patients, and other individuals wanting to learn more about plant-based treatments for diabetes mellitus.-9+6+3